THE INFLUENCE OF PRODUCT BUNDLING OF IPHONE AND TELKOMSEL ON CONSUMER SATISFACTION IN MANADO - Doodoh, Dian Victory (Universitas Sam Ratulangi, 2014)
Companies are vying to sell their products with the cheapest price, because they want to increase the number of sales. Marketing strategy that involves offering several product and services for sale as one combined product we called product bundling. This research is conduct in Manado. The objectives of this research are to analyze the influence of Product Bundling on Consumer Satisfaction with case study iPhone and Telkomsel, partially and simultaneously. This research is a causal type of research where it will investigate the influence of product bundling on consumer satisfaction. Using a multiple regression model to answer the research problem. The population in this study is a consumers of iPhone bundling Telkomsel in Manado, whereas samples taken by each respondent 100 respondents. The hypothesis testing, this research conduct a conclusion of there is a significant influence of Product Assortment and Choice simultaneously and partially on Consumer Satisfaction. This study reveals that choice is a mental decision that made by the consumer has a strong influence factor in order to buy a product, when consumer go for purchasing, they prefer to purchase a product with a well know branded, good service and collaborating of product bundling. Keywords: consumer satisfaction, product assortment, product bundling.